A Comparison of Some Important Biochemical Indicators According to Escalating Physical Effort till Fatigue for Elite Freestyle Wrestlers, 800m Runners, and 200m Freestyle Swimmers - Curby, David; Ali, Ahmed; Khudair, Ghazwan (Journal of Physical Education, 2024)
It is the nature of the game and the activity that determines the characteristic of the manifestation of fatigue according to what is required by the neuromuscular work in it, as well as the changes that occur in the functional variables and the time of the differential threshold. The location of each activity and the game of these teams have been studied in a special table for energy production systems as a result of continuous changes in their laws, and are considered within the energy systems such as the anaerobic system (Phosphagine) and lactic acid for (800) m runners - freestyle swimmers (200) m in the physical effort till fatigue. The comparison in the important functional indicators for them, and the research methodology embodied in the way of working through the method used, which is the descriptive method in comparison then, the researchers identified the research community for the young national team athletes for freestyle wrestling, and the national team(800)m runners, as well as of the national team in (200) m swimming for the sports season (2022-2023), A total of 21 athletes were selected in an organized manner and distributed into three equal groups (7 athletes) for each of the three types of sports (wrestler, 200-meter swimming and 800-meter running)., and the researchers would conduct tests for the research variables biochemical for the sample members, as well as some variables that have an impact on the results of the study such as (height, age, weight, and the age of training ), and the homogenization of the research sample members was carried out. The results of statistical treatments were presented, analyzed, and discussed, supported by sources. The most important conclusions were that most of the activities and the variation of values are very essential biochemical indicators. The differences were significant and the positive variation in accordance to the type of sport or activity, and the last variation between the activities in terms of comparison in these variables is due to the nature and specificity in terms of the intensity of the resistances and direct and indirect friction For competitors and the expenditure of energy stored in muscles. Finally, the researchers recommended knowing the most important biochemical indicators in these events and sports as they reflect a clear picture of the individuals’ internal preparations and functional responses.